The influence of projectile impact velocity and target characteristics on the terminal ballistics parameters of small-caliber projectile - Faris Memic; Alan Catovic (Defense and Security Studies, 2024)
The study examines the results of numerical simulations of the penetration of a 7,62mm x 63, AP, M2 projectile through a target. Model validation involved a numerical simulation of 7,62mm x 63, AP, M2 projectile penetration through an AA5083H116 target, for which experimental results were available in the literature. The results of the numerical simulation were used for regression analysis - to calibrate the Recht-Ipson model for the given projectile. Furthermore, penetration analyses of 7,62mm x 63, AP, M2 projectiles through various target materials were performed at consistent projectile velocities and mesh sizes. As expected, bainitic steels exhibited the highest resilience, demonstrating that increased material hardness and tensile strength correlate with enhanced projectile penetration resistance.